Enhancement of landfill gas generation from aged waste by a combination of moisture adjustment and application of biochar and neutral red additives: A field-scale study. (1st January 2021) - Rasapoor, M.; Young, B.; Brar, R.; Baroutian, S.
Highlights: Maximum CH4 content in LFG (60.2%) achieved using NR diluted in compost leachate. Compost leachate used for moisture adjustment was effective on landfill settlement. The radius of influence of applied vacuum increased via application of NR (36 m). Using biochar was impactful on improving the LFG generation rate at the beginning. Temperature and CO content in LFG increased for all liquid enhanced experiments. Abstract: Many landfills suffer from a sharp drop in landfill gas generation after an initial period of gas generation. A field-scale study was conducted to investigate the effects of moisture adjustment using stormwater and compost leachate, and additives (neutral red and biochar) on landfill gas quality and quantity. Five different gas wells and five vertical leachate-infiltration wells were drilled to implement moisture addition treatments. During 20 weeks of field study, addition of compost leachate resulted in a significant landfill settlement (24 cm). Mixture of leachate and biochar increased the rate of landfill gas generation at the start of the experiment and increased the total gas flow rate by more than 2.8 times. Neutral red diluted with compost leachate decreased the rate of landfill gas generation compared to pure leachate, but it resulted in more stable landfill gas generation at the end of the experiment. Application of neutral red and biochar additives maximised the methane content to 60.2% and 59.3% of the total landfill gas volume, respectively. However, O2 reached zero for all the liquid-added wells and then increased at the end of the experiment. Temperature and CO content increased for all the liquid-added experiments due to the higher degradation rate compared to the control experiment. Moisture adjustment significantly increased the gas wells' radius of influence. The maximum radius of influence was 36 m for neutral red application. Biochar mixed with leachate showed the least impact on the radius of influence because of the insolubility of biochar in leachate.